Current overview of osteoradionecrosis of the jaws: An integrative literature review (Research, Society and Development, 2023)
Cancers receive their nomenclature according to the type of cells, tissues and region in which they are found. There are some types of treatments for cancer patients, called oncotherapies, the main ones being surgery, chemotherapy and radiotherapy. Osteoradionecrosis (ORN) is considered one of the most serious complications of radiotherapy (RT), characterized by bone exposure through an opening in the skin or mucosa, a persistent wound that does not heal for three months or more. The aim of this study was to evaluate new parameters related to osteoradionecrosis, such as risk factors, new therapies and available tools. This is an integrative literature review, where the terms: "Therapies" AND "Osteoradionecrosis" were used, with a language filter in Portuguese and English, published in the last year. The responsible professional must be aware of the most current parameters in the literature , drawing attention to the study of signs, symptoms, diagnosis, risk factors and treatments.